Circumventing sinkhole attack in ad hoc networks. (2015) - Rana, Khurram Gulzar; Yongquan, Cai; Ditta, Allah; Azeem, Muhammad; Qasim, Muhammad
Ad hoc networks are a wireless technology foreseen to be used increasingly in the near future due to their data acquisition and processing abilities. Ad hoc networks are infrastructure-less networks and they suffer from several types of routing attacks. We investigate the problem of defending ad hoc networks against sinkhole attacks that disrupt dynamic routing protocol. We propose a novel method (AODV-SDR) that detects and removes sinkhole attack without using any type of encryption, keying mechanism or hashing function. We work on AODV route discovery phase and malicious node is detected by great change in destination sequence number. We show that our scheme can detect false sink with great accuracy. This approach is very useful because it has no overhead of encryption and hashing.